A Novel Quinolyl‐Substituted Analogue of Resveratrol Inhibits LPS‐Induced Inflammatory Responses in Microglial Cells by Blocking the NF‐κB/MAPK Signaling Pathways. Issue 20 (16th August 2019) - Hou, Yue; Zhang, Yuchen; Mi, Yan; Wang, Jian; Zhang, Haotian; Xu, Jikai; Yang, Yanqiu; Liu, Jingyu; Ding, Lingling; Yang, Jingyu; Chen, Guoliang; Wu, Chunfu
Abstract : Scope: The anti‐neuroinflammatory effect of a novel quinolyl‐substituted analogue of resveratrol (RV01) on lipopolysaccharide (LPS)‐induced microglial activation is investigated, as well as the possible underlying mechanisms. Methods and results: Cell viability is measured using an MTT assay. Nitric oxide (NO) release is determined by nitrite assay. The interaction between RV01 and inducible nitric oxide synthase (iNOS) is studied using molecular docking. Free radical scavenging activity and reactive oxygen species (ROS) production are determined by DPPH reduction assay and DCFH‐DA assay. Pretreatment with RV01 (1–30 µm ) prior to LPS (1 µg mL –1 ) stimulation decreased NO release and iNOS expression without observable cytotoxicity. RV01 reduced the mRNA levels and secretion of tumor necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6). RV01 also inhibited LPS‐induced ROS production and nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation. Furthermore, RV01 decreases the protein expression of toll‐like receptor 4 (TLR4) and inhibits the LPS‐induced activation of the mitogen‐activated protein kinase (MAPK) and nuclear transcription factor‐κB (NF‐κB) signaling pathways. Additionally, conditioned medium from microglia co‐treated with LPS and RV01 alleviates the death of SH‐SY5Y cells induced by conditioned medium from activated N9 microglial cells. Lastly, a mouse neuroinflammation model is further used to confirm the effect of RV01 in vivo. Conclusion: These results show that RV01 suppresses microglia‐mediated neuroinflammation and protects neurons from inflammatory damage, which indicates that RV01 has great potential as a nutritional preventive strategy for neuroinflammation‐related diseases. Abstract : RV01, a novel quinolyl‐substituted analogue of resveratrol, exhibits an anti‐neuroinflammatory effect induced by lipopolysaccharide (LPS) both in vitro and in vivo. RV01 decreases TLR4 protein expression, attenuates ROS production, inhibits NADPH oxidase activation, suppresses the corresponding downstream MAPKs and NF‐κB pathways, and subsequently reduces the secretion of pro‐inflammatory mediators in LPS‐activated microglia.